Bird Box : Bird Box #1 - Malerman, Josh (New York, NY : Ecco, an imprint of HarperCollinsPublishers, 2014)
In a world where no one can go outside for fear of something terrifying that when seen drives people to deadly violence, single mother Malorie and her two children must attempt a terrifying twenty-mile trip downriver while blindfolded.
Keywords: Suspense fiction; Dystopian fiction; Mystery fiction; Horror fiction